2011
DOI: 10.1016/j.pain.2010.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of pregabalin in patients with central post-stroke pain

Abstract: Pregabalin has demonstrated efficacy in several forms of neuropathic pain, but its long-term efficacy in central post-stroke pain (CPSP) is unproven. We evaluated the efficacy and safety of pregabalin versus placebo in patients with CPSP. A 13-week, randomized, double-blind, multicenter, placebo-controlled, parallel group study of 150 to 600 mg/day pregabalin was conducted in patients aged ≥18 years with CPSP. The primary efficacy endpoint was the mean pain score on the Daily Pain Rating Scale over the last 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
3
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(66 citation statements)
references
References 29 publications
0
58
3
5
Order By: Relevance
“…However, so far no evidence has been provided to support the use of gabapentinoids in the treatment of central neuropathic pain of thalamic damage caused by either ischemic or hemorrhagic stroke. In a 13-week, randomized, doubleblind, multicenter, placebo-controlled trial, treatment with pregabalin did not provide significant pain relief in patients with CPSP [19].…”
Section: Gabapentinoid Insensitivity In Central Neuropathic Pain Of Tmentioning
confidence: 92%
See 1 more Smart Citation
“…However, so far no evidence has been provided to support the use of gabapentinoids in the treatment of central neuropathic pain of thalamic damage caused by either ischemic or hemorrhagic stroke. In a 13-week, randomized, doubleblind, multicenter, placebo-controlled trial, treatment with pregabalin did not provide significant pain relief in patients with CPSP [19].…”
Section: Gabapentinoid Insensitivity In Central Neuropathic Pain Of Tmentioning
confidence: 92%
“…In 2004, gabapentinoids were also approved as first-line drugs for the treatment of some types of neuropathic pain, such as painful diabetic neuropathy, post-herpetic neuralgia, and spinal cord injury-induced pain [3,14,15,18]. Nonetheless, gabapentinoids are commonly used to treat other types of In a recent placebo-controlled trial, pregabalin failed to show significant improvement over placebo in patients with CPSP [19]. More recently, we evaluated the anti-allodynic effects of GBP in rats with CPSP hypersensitivity induced by experimental thalamic hemorrhage and found that, although GBP had a dose-dependent anti-allodynic effect following a single systemic administration, the effectiveness was transient, gradually decreasing after repeated administration for 14 days, implying the existence of drug insensitivity [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the clinic, CPSP is usually treated with adjuvant analgesics, such as antidepressants, antiepileptogenics and narcotic analgesics, based on the treatment of neuropathic pain or surgery. 4,[9][10][11][12] However, the effect of adjuvant analgesics on the BCAO-induced pain is unclear.…”
mentioning
confidence: 99%
“…After reviewing the full texts, we deemed 8 English language studies that enrolled 459 patients with CPSP eligible for our review (Table 1). [37][38][39][40][41][42][43][44] There was almost perfect agreement (Φ=0.82) between reviewers at the full-text review stage. All trials evaluated treatment effects on pain, and none reported effects on physical functioning, role functioning, or interpersonal functioning (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported no difference in the number of participants (in the pregabalin and placebo groups) who presented with psychiatric comorbidities, specifically depression and insomnia. 41 Figure 3 portrays the risk of bias assessment.…”
Section: Resultsmentioning
confidence: 99%